Electro-thermal and optical characterization of an uncooled suspended bolometer based on an epitaxial La0.7Sr0.3MnO3 film grown on CaTiO3/Si. (10th November 2020) - Nascimento, V M; Méchin, L; Liu, S; Aryan, A; Adamo, C; Schlom, D G; Guillet, B
Abstract: The electro-thermal and optical properties of a bolometer based on an La0.7 Sr0.3 MnO3 ( LSMO) thin film with a detection area of 100 × 100 µ m 2 are presented. The LSMO thin film was epitaxially grown on CaTiO3 /Si and patterned using a two-step etching process of ion-beam etching in argon and of reactive-ion etching in SF6, in order to etch LSMO/CaTiO3 and Si, respectively. The voltage-current ( V – I ) characteristics of the bolometer were measured in vacuum from 240 K to 415 K. From the V – I characteristics and a thermal model of the bolometer, the electrical responsivity was determined and compared to the optical responsivity measured with a laser diode at 635 nm. The noise equivalent power (NEP) as a function of frequency was measured by dividing the spectral noise power density by the optical responsivity. At 300 K and a bias current of 80 µ A, the NEP was 2.3 × 10 −11 W · Hz −1/2 in the 20–200 Hz modulation frequency range and the response time was 1.3 ms. The obtained NEP value without any absorbing layer or antennas, combined with the low value of the response time, are a very promising step towards the use of such LSMO-based bolometers for IR or THz detection.